Rs4911154 of circ-ITCH aggravated tumor malignancy of thyroid nodules via the circ-ITCH/miR-22-3p/CBL axis - Yiqing Guo (Nature Portfolio, 2021)
Abstract Recent evidence revealed an inhibitory effect of circ-ITCH on the progression of papillary thyroid cancer via affecting the circ-ITCH/miR-22-3p/CBL axis. Rs4911154, an SNP located in circ-ITHC, was previously reported to be significantly associated with an increased risk of hepatocellular carcinoma. Ultrasound testing was used to evaluate the doubling time of thyroid nodules. 202 patients diagnosed with thyroid nodule disorders were divided into three groups according to their genotypes at rs4911154. We found that the A allele was correlated with a shortening doubling time of thyroid nodules. Moreover, the A allele contributed to reduced expression of circ-ITCH/CBL and increased expression of miR-22-3p. Besides, decreased tissue apoptosis was linked to the A allele. Luciferase assays indicated that miR-22-3p could effectively suppress the luciferase activities of CBL and circ-ITCH. Furthermore, manual up-regulation of miR-22-3p effectively suppressed the expression of CBL, while CBL siRNA apparently abolished circ-ITCH induced CBL upregulation, reduced proliferation and increased apoptosis of K1 and TPC-1 cells. A signaling pathway of circ-ITCH/miR-22-3p/CBL axis was established to explain the effect of SNP of circ-ITCH in thyroid tumor malignancy. Compared with the G allele, the A allele in rs4911154 contributed to the malignancy of thyroid nodules with decreased doubling time and down-regulated CBL expression.